Trochanteric hip fracture during cardioversion therapy. A case report. (2017) - Gómez, J.; Albareda, J.; Ezquerra, L.
Highlights: The propofol sedation should be complemented with skeletal muscle relaxants in the cardioversion therapy to avoid hip fracture in select patients with osteoporosis. Hip fracture in osteoporotic bones should be considered after muscle violent contraction that causes hip pain and functional impotence. Abstract: Introduction: Trochanteric hip fractures in elderly patients with osteoporosis are commonly caused by low energy trauma. The cardioversion therapy is an extremely rare cause of this type of fracture. Presentation of case: We report the case of a woman with hip fracture after cardioversion. Discussion: We discuss the production mechanism of this injury and the importance of the care of the osteoporotic bone under these therapies. Conclusion: The propofol sedation should be complemented with skeletal muscle relaxants in the cardioversion therapy to avoid hip fracture in select patients with osteoporosis.